The 1994 Bolivia deep focus earthquake at 8.2 Mw - Jimenez, C. (2014)
The 1994 Bolivia earthquake, with hypocenter at 641 km depth, is the greater magnitude earthquake recorded instrumentally in the last 50 years. This earthquake did not produce damage in the surface but was perceived in most of the southern hemisphere. This seismic event had a multiple (complex) rupture process during 55 s and the rupture propagated towards N-E direction with a 1.6 km/s mean velocity. The size of the rupture was around 90 km; however, the principal asperity was contained within an area of 40×40 km2. The rupture corresponds to a focal mechanism of normal type with planes oriented in the E-W direction, being the fault plane close to the vertical. The scalar seismic moment calculated by teleseismic body waveform inversion is 2.30 × 1021 Nm and corresponds to a magnitude of Mw 8.2.